Development of Building Inventory Data in Ulaanbaatar, Mongolia for Seismic Loss Estimation - Zorigt Tumurbaatar; Hiroyuki Miura; Tsoggerel Tsamba (ISPRS International Journal of Geo-Information, 2021)
During the last two decades, the rapid urbanization movement has increased the concentration of population and buildings in Ulaanbaatar city (UB), Mongolia. There are several active faults around UB. The estimated maximum magnitude of 7 in the Emeelt fault has been expected to significantly impact the UB region because the fault is only 20 km from the city. To consider the disaster mitigation planning for such large earthquakes, assessments of ground shaking intensities and building damage for the scenarios are crucial. In this study, we develop the building inventory data in UB, including structural types, construction year, height, and construction cost in order to assess the buildings’ vulnerability (repair cost) due to a scenario earthquake. The construction costs are estimated based on the procedure of the Mongolian construction code from the coefficients of cost per floor area for each structural type, and coefficients for heating system, floor areas, and buildings’ locations. Finally, the scenario’s economic loss of the damaged buildings is evaluated using the developed building inventory, global vulnerability curves of GAR-13, and estimated spectral accelerations.